Linear Programming dengan Metode Primal Simplex Kasus Minimasi (Studi Kasus UMKM Ice Cream Putri) - Pesta Gultom; Dewi Sinta Sianipar; Yokhebeb Zega; Prycillia Putri Dwi Vani; Bernadetha Manurung (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a significant role in the economy, including MSMEs in the culinary sector such as Putri Ice Cream Business. Decision making related to optimal resource allocation is crucial to increase the efficiency and profitability of MSMEs. This study aims to apply the linear programming method with the primal simplex algorithm to minimize production costs in the case study of Putri Ice Cream MSME. The objective function is to minimize the total production cost, as well as the limitations related to the availability of main raw materials and machine production capacity. Data on main raw materials and machine production capacity were obtained from the Putri Ice Cream MSME which was the case study. The results of the study show that the application of the primal simplex method produces an optimal solution that provides recommendations for product combinations for each type of Putri Ice Cream with minimal production costs. Sensitivity analysis was also conducted to test the stability of the optimal solution to changes in capital. This study provides a practical contribution to Putri Ice Cream MSME in optimizing their resource allocation and increasing cost efficiency through a quantitative approach.